Standard terminologii w pielęgniarstwie - Bartz, Claudia C.; Youn Kim, Tae; Kilańska, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2017)
ICN anticipates that ICNP® users will develop more catalogues as more nurses use ICNP® in electronic health records and digital communication devices. Nurses who use ICNP® in the documentation of their practice should know the core data elements for their specialty or setting. The following questions needed to be answered: “What nursing diagnoses are most commonly used?”, “What nursing interventions are used?” and “What care recipient outcomes are used in that specialty or setting?” Since ICNP® was first released in 2005, many pre-coordinated statements have been added to the terminology and more catalogues have been developed by nurse experts and published by ICN. The critical need for continued development of ICNP® is the use of the terminology in clinical settings so that the collection of standardized data is available for analysis and research. In this way, nursing will be described. Nurses will then be able to say: “these are our most common diagnoses and interventions” and “these are the best or most-preferred care recipient outcomes.”